Comparative Global Perspectives on Community Involvement in Language Formation among Primary Learners - Sentasas, Ma. Elena; Galigao, Dr. Regina (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the role of community involvement in language formation among primary learners across diverse global contexts. Specifically, it explored the conceptual foundations and global patterns of community engagement, the challenges and gaps in community-based language practices, and the cultural and contextual factors influencing literacy and identity formation. Using a data mining research design, qualitative and quantitative data were extracted and analyzed from peer-reviewed articles, books, and institutional reports published between 2019 and 2025. The analysis revealed five interconnected factors that significantly support language development: family involvement, mother-tongue instruction, cultural storytelling, school community partnerships, and technology integration. These factors contribute to improved literacy outcomes, learner engagement, cultural identity, and language preservation across multilingual and multicultural settings. The study also identified persistent challenges, including resource limitations, inadequate numbers of trained bilingual teachers, risks of language loss, and unequal access to technology. Despite contextual differences across regions, community engagement emerged as a consistent and influential factor in strengthening language education. Based on the findings, a training framework was proposed to enhance collaboration among educators, families, and communities through culturally responsive teaching, storytelling, mother-tongue education, and responsible technology use. The study concludes that sustained school community collaboration can foster inclusive and culturally grounded learning environments that support literacy development and learner success. The study aligns with Sustainable Development Goal 4 (Quality Education) by promoting inclusive, equitable, and culturally responsive approaches to language learning. Its sustainability contribution lies in strengthening educational, cultural, and community sustainability through literacy development, language preservation, and long-term collaboration among schools, families, and communities.
Keywords: Community Engagement; Cultural Identity; Language Development; Literacy Development; Mother Tongue Education; Primary Learners; School Community Partnerships